(untitled) (Journal of NELTA, 2018)
As a high school teacher, I have always found teaching poems a source of developing language skills and different aspects too, including grammar, vocabulary and even communicative functions. Further, I have a feeling that teaching poems helps to develop creative, critical and analytical skills of students at this level. Reading a poem is not to try to solve or explain what is written; rather it should be a process of demystification so that the students enjoy reading as well as are encouraged to write their own poems. I have often found the expressions of teenagers in the form of poems their frustrations, emotions, empathy and inner feelings — to be one way of sharing unspoken words. This lesson takes an example of a poem from a 10th grade class and focuses on how a lesson on teaching poetry can be taught effectively to enhance creative, critical and analytical skills, and to create awareness of literary devices at secondary and post-secondary levels. The lesson incorporates activities and possible strategies to boost higher levels (analysis, evaluation and creation) of thinking rather than “over emphasizing the language teaching aspects” (Ur, 1996). Journal of NELTA , Vol. 22, No. 1-2, 2017 December, page: 135-139